Modelling Team Effectiveness and its Determinants Among Multidisciplinary Engineering Students: A Case of Malaysian Public University - Mohammed Hussein, Shawqi; Mohd Daud, Salwani; Mantoro, Teddy; Azmeela Shariff, Sya; Hasan, Mahmudul (International Journal of Engineering and Technology, 2018)
Team effectiveness depends on the performance of each team member. Success or failure of a team highly relies on the interaction level of all members. Effective teamwork is a critical learning outcome for engineering students and it is one of the most desired skill required by employers. All engineering graduates must have the ability to function in multidisciplinary teams. Prior studies had also found that, many Malaysian employers agreed that the lack of team working skill among the Malaysian graduates would risk the survival of an organisation and in result developing low-level interpersonal skills which is equally necessary for working effectively in a team. However, in the engineering education literature most of the previous studies have focused on the area of professional environments. A very few studies were conducted in the context of educational environments to identify the factors that affect the team effectiveness in higher education. Moreover several internal and external factors also inï¬‚uence the outcomes of student teamwork and not every group is effective in their objectives and numerous groups fail. Therefore, this study is designed to identify the underlying factors that help students to develop their teamwork skill, thus improving team effectiveness. Hence, upon analysing the articles found in this study, nine (factors were identified to have more impacts towards team effectiveness, which were (1) team communication, (2) trust, (3) team cohesion, (4) team leadership, (5) team coordination and cooperation, (6) team commitment, (7) team performance, (8) team satisfaction, and (9) task interdependence. In addition, after comparing several models and theories, a conceptual model that demonstrates relationships among the identified factors was proposed. It asserted team performance and team satisfaction as the predictors of team effectiveness.Â Â